Distribusi dan Kondisi Kesehatan Mangrove di Utara Labuan Bajo, Nusa Tenggara Timur - Pura, I Putu Yogadisa; Arthana, I Wayan; Putra, I Nyoman Giri (Journal of Marine Research and Technology; Vol 5 No 2 (2022): AUGUST 2022, 2022)
This study aimed to determine the distribution , health condition, and mangroves' environmental co nditions in northern Labuan Bajo. The mangrove species found at the observation site s were Rhizophora apiculata, R . stylosa, R . mucronata. Ceriops tagal, Sonneratia alba, Bruguiera gymnorrhiza, Xylocarpus granatum, X . moluccenis, Phemphis acidula. Mangroves north of Labuan Bajo are classified as healthy with moderate to good criteria ranging from 60.48% - 79.11%; the value of mangrove health is determined from several parameters such as canopy cover, which has a range of cover values ranging from 68.22% - 84.73% with an average percentage of the overall canopy cover at all observation points 79.72%, the density has a range value between 650 ponhon/ha -7950 trees/ha. The average tree diameter of the overall diameter of the grove reaches 844 cm. with an average environmental parameter value such as temperature reaching 31.03 °C, salinity is 34.4, pH average of 7.06 with the substrate in the entire observation area dominated by a muddy type of substrate that supports the growth of this species in addition to mangroves Rhizophora sp. species has excellent adaptability to the environment which causes this species to dominate in the observation area .